John F. Kennedy : the politics of confrontation and conciliation - Lord, Donald C. (Woodbury, N.Y. : Barron's, 1977)
An account of the life and times of John F. Kennedy stressing his political career and including chapters on image-making and the verdict of history.
Running title: Shapers of history.
Includes index.
Bibliography: p. 406-435.
Keywords: Kennedy, John F. -- 1917-1963.; Kennedy, John F. -- 1917-1963.; Presidents; United States -- Politics and government -- 1961-1963.; United States -- Foreign relations -- 1961-1963.; United States -- Politics and government -- 1961-1963.; United States -- Foreign relations -- 1961-1963.